1970
DOI: 10.3329/jbs.v17i0.7110
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variability, Diversity and Association of Quantitative Traits with Grain Yield in Rice (<i>Oryza sativa</i> L.)

Abstract: Context: Genetic diversity is pre-requisite for any crop improvement programme as it helps in the development of superior recombinants.Objectives: Recognizing the importance of genetic diversity in plant breeding experiments, the present research work was taken up to estimate genetic diversity in different accessions of rice for various agroeconomically important characters. Materials and Methods:Experiments were carried out with 40 Rice (Oryza sativa L.) genotypes which were evaluated for yield and yield cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
30
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 3 publications
8
30
0
Order By: Relevance
“…The observed differences among the genotypes may be attributed to their different geographical origin. Similar reports on phenotypic variation among rice genotypes were observed by Elayaraja et al, (2005) and Pandey et al, (2009).…”
Section: Resultssupporting
confidence: 77%
“…The observed differences among the genotypes may be attributed to their different geographical origin. Similar reports on phenotypic variation among rice genotypes were observed by Elayaraja et al, (2005) and Pandey et al, (2009).…”
Section: Resultssupporting
confidence: 77%
“…Genetic variation is the basis of plant breeding and provides a great array of genotypes that can be selected to develop new varieties or breeding materials [8]. Variability in terms of genetic divergence for agronomic traits is the key component of breeding programmes for broadening the gene pool of rice and requires reliable estimates of heritability to plan an efficient breeding programme [9].…”
Section: Introductionmentioning
confidence: 99%
“…Previously, Pandey et al (2009) reported highly significant difference among 40 genotypes of rice for 12 quantitative traits. Sohrabi et al (2012) evaluated 50 Malaysian upland rice accessions for 12 growth, yield and yield component traits and observed significant and highly significant deference among the accessions for all the traits.…”
Section: Results and Discussion Analysis Of Variance Of Morpho-physicmentioning
confidence: 96%